The effects of load biaxiality and plate length on the limit load of a centre-cracked plate. (October 2015) - Meek, C.; Ainsworth, R.A.
Highlights: Upper and lower bound limit loads of a plane strain centre-cracked plate estimated. Finite element limit loads shown to be often close to upper bound solution. Effects of plate length and a wide range of load biaxiality addressed. Abstract: Fitness-for-service codes need to treat the effects of multiaxial stress on the limit load. This paper examines the effects of a wide range of biaxial loading and plate length on the limit load of a centre-cracked plate in plane strain. Solutions are obtained from upper and lower bound theorems of limit analysis and finite element analysis. The bounds are exact for a range of biaxial stress ratios including all negative biaxiality for long plates. At high positive biaxiality, the upper and lower bounds also converge. For loadings close to equal biaxiality, the limit load is significantly elevated by the biaxiality.